An Early Warning Elephant Intrusion Integrated with IoT - Mohd Zulhafizie; Fauziahanim Che Seman, (Vol. 1 No. 1 (2019): Internet of Things: Tracking & Monitoring, 2022)
Human–animal conflict (HEC) is one of the main issue in the forest border areas where herds of wild elephants straying into human habitation. Another issues is that the elephant start to raid the villager’s plantation. The main idea of this project is to design a prototype of an early warning detection and prevention system that prevent elephant intrusion at the same time alerts the villagers.  The system also be able to integrate with Internet of Things (IoT). In this proposed system, a Passive Infrared (PIR) sensor or motion detection sensor being used to capture the movement of the elephant. The prevention mechanism is conducted by Arduino Uno R3 ATMega328P as microcontroller and later communicate with the other microcontroller via nRf2401 modules. The system is connected with cloud database using Favoriot platform. The platform communicate with Arduino Uno ATMega328P via NodeMCU ESP8266 Wi-Fi to obtain the Wi-Fi signal for uploading the data of intrusion events. The average of uploading time for the data for Favoriot platform is within 10 seconds until 15 seconds. The systems able to alerts the local villagers and triggers prevention mechanism at the same time when the elephant intrusion event occurs. The data intrusions is uploaded to Favoriot platform on regular bases and specifically extract the data making into real time analysis.